Організаційно-економічний механізм цифрової трансформації промислових підприємств - Попело, Ольга; Самойлович, Олександр (Науковий вісник Полісся, 2025)
In the article, features of formation of digital transformation of industrial enterprises are examined. Changes that affect industrial enterprises by accelerating or restraining digital transformation are outlined, namely strategic, operational and organizational. The organizational and economic mechanism for digital transformation of industrial enterprises is developed. It is argued that the mechanism structure should contain three key blocks of tools: management tools, financing tools and technical support tools, which effectiveness is determined by efficient use of supporting components and implementation of basic principles of digital transformation. It is argued that management, financing and technical support tools form a triad that ensures successful implementation of digital transformation of the industrial enterprise. It is emphasized that when forming organizational and economic mechanism for digital transformation, industrial enterprises should be guided by the system of principles that determine the approach to implement digital technologies, resource management and development of organizational culture, and are aimed at ensuring consistency, efficiency and sustainability of changes.